A Comment on "A Systematic Review and Meta-Analysis of Transdiagnostic Cognitive Behavioural Therapies for Emotional Disorders" - František Bartoš; Henrik R. Godmann (Institute for Replication (I4R), 2025)
Schaeuffele et al. (2024) examined the effect of Transdiagnostic Cognitive Behavioural Psychotherapy (TD-CBT) on emotional disorders through a meta-analysis of 53 studies involving 6,705 participants. Their main findings indicated that TD-CBT has larger treatment effects on depression, g = 0.74, 95% CI (0.57, 0.92), p ﹤ 0.001, and anxiety, g = 0.77, 95% CI (0.56, 0.97), p ﹤ 0.001, than controls. We replicated the data extraction of summary information from a subsample of the original studies with only minor deviations and we successfully computationally reproduced the main claims of the paper using the original data. However, robustness analyses adjusting for publication bias led to substantially different conclusions. In contrast to the original authors, we found weak evidence for the absence of the overall treatment effect of TD-CBT on both depression and anxiety in most of the specified models. Although additional sensitivity analyses could not completely rule out that the observed differences are partially results of small-study effects, further examination of between-study heterogeneity did not reveal consistent evidence of the benefit of TD-CBT when compared to any of the comparisons groups.
Keywords: 330; Depression; Anxiety; Publication Bias; Bayesian; Heterogeneity